Study on the improvement code of practices in structural design and material specifications - Nurul Atiqah , Ajis (2012)
In Malaysia, most of the design concrete structure is based on Code of Practice British Standard (BS 8110). In line with the change of time and technology, Malaysia has been introduced to Eurocode 2 (EC 2) as a new guideline in design concrete structures. However, EC2 still in early stage of implementation therefore, it widely introduced to the engineers and in the higher institutions. The main objective of this study is to find the differences between BS 8110 and EC 2 in the aspect of materials and design specifications. There have few differences identified and studies have been conducted to find out the causes and reasons of the changing. The main differences between BS 8110 and EC 2 in the design specifications is BS 8110 designed based on structure element such as beam, column, slab and others. While, EC 2 designed based on phenomenon such as flexure, shear, deflection and axial force. In terms of material, there is change in partial factor of safety for reinforcing steel. Partial factor of safety for reinforcing steel in EC 2 is higher compare with value use in BS 8110. However, this difference neutralized by the reinforcing steel with f k = 500 N/mm 2 . In addition, there are many factors need to be consider in EC 2 compare with BS 8110.